2014
DOI: 10.4172/2329-6674.1000123
|View full text |Cite
|
Sign up to set email alerts
|

Drug Discovery and In Silico Techniques: A Mini-Review

Abstract: Use of Computational (in silico) methods are widely applied in drug discovery. In drug discovery process, identification of the suitable drug target is the first and foremost task. These targets are biomolecules which mainly include DNA, RNA and proteins (such as receptors, transporters, enzymes and ion channels). Validation of such targets is necessary to exhibit a sufficient level of 'confidence' and to know their pharmacological relevance to the disease under investigation. The aim of this mini-review is to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 19 publications
(23 reference statements)
0
6
0
1
Order By: Relevance
“…The application of computational (in silico) methods in providing structural insights into the binding of small molecule inhibitors has gained prominence in the drug discovery process in recent years. Insights from computational reports can aid in the optimization of existing small molecule compounds to yield enhanced and improved novel small molecule inhibitors and eventually improve the overall efficiency of the drug discovery process . Computational approaches have been employed in the study of several conditions and for varying purposes including mutational studies and the identification of new inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…The application of computational (in silico) methods in providing structural insights into the binding of small molecule inhibitors has gained prominence in the drug discovery process in recent years. Insights from computational reports can aid in the optimization of existing small molecule compounds to yield enhanced and improved novel small molecule inhibitors and eventually improve the overall efficiency of the drug discovery process . Computational approaches have been employed in the study of several conditions and for varying purposes including mutational studies and the identification of new inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…The targets can be identified at different levels, ranging from molecular to cellular to whole-organism levels [ 107 ]. Once these targets are identified, suitable molecules that interfere in its working can be identified [ 108 ]. In silico methods can facilitate faster drug development by making predictions for a large set of drug candidates without the need of chemically synthesizing each of the compounds [ 109 ].…”
Section: Models For Drug Discovery Against Ntmmentioning
confidence: 99%
“…[16] In silico methods are extensively used for in vitro and in vivo studies to get the preliminary predictions of results of gross activities such as physicochemical characterization, toxicity properties, affinity to a target receptor or protein, the elucidation of absorption, distribution, metabolism and excretion. [17] In silico prediction of the toxicity is carried out to get a gross idea of the highest dose of paeonol that can be used in long-term studies without or less overt signs of toxicity. [22] In the current study, in silico prediction of the maximum tolerated human dose of paeonol was found to be 0.813 (log mg/kg/ day).…”
Section: Histopathological Studymentioning
confidence: 99%